Formulation Development and in vitro Evaluation of Drug Release Kinetics from Sustained Release Aceclofenac Matrix Tablets using Hydroxypropyl Methyl Cellulose (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The objective of the present study was to develop a once-daily sustained release matrix tablet of Aceclofenac using hydroxypropyl methyl cellulose (Methocel K 100M CR) as release controlling factor and to  evaluate drug release parameters as per various release kinetic models. The tablets were prepared by direct  compression method. The powder blends were evaluated for angle of repose, loose bulk density, tapped bulk density,  compressibility index, total porosity and drug content etc. The tablets were subjected to thickness, weight variation test, drug content, hardness, friability and in vitro release studies. The in vitro dissolution study was carried out for 24  hours using United States Pharmacopoeia (USP) 22 paddle-type dissolution apparatus in phosphate buffer (pH 7.4). The powder blends showed satisfactory flow properties, compressibility index and drug content etc. All the tablet formulations showed acceptable pharmacotechnical properties and complied with pharmacopoeial specifications. The results of dissolution studies indicated that the formulation F-3 (40% Methocel K100M CR of total weight of tablet) could extend the drug release up to 24 hours and the total release pattern was very close to the theoretical release profile. By comparing the dissolution profiles with the originator brand of Arrestin SR, the formulation F-3 exhibited drug release profile like originator brand. From this study, a decrease in release kinetics of the drug was observed by  increasing the polymer concentration. Kinetic modeling of in vitro dissolution profiles revealed the drug release mechanism ranges from diffusion controlled or Fickian transport to anomalous type or non-Fickian transport, which  was only dependent on the type and amount of polymer used. The drug release followed both diffusion and erosion  mechanism in all cases. The drug release from the formulation (F-3) was satisfactory after 3 months storage in 400C  and 75% RH. Besides, this study explored both of the optimum concentration and effect of polymer(s) on  Aceclofenac release pattern from the tablet matrix for 24 hour period. The matrix tablet of Aceclofenac using HPMC  with molecular weight of K100M controlled the drug release effectively for 24 hours; hence the formulation can be  considered as a once daily sustained release tablet of Aceclofenac in order to improve patient compliance. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12485 Dhaka Univ. J. Pharm. Sci. 11(1): 37-43, 2012 (June)